Vouchers for Basic Education in Developing Economies : An Accountability Perspective - Gauri, Varun (World Bank, 2013)
Advocates argue that voucher programs can correct the incentive problems of education systems in developing economies. An accountability perspective, based on a principal-agent framework, was developed to clarify the arguments for and against education vouchers. An assessment of findings on voucher programs in industrial countries and a review of voucher or quasi-voucher experiences in Bangladesh, Chile, Colombia, Côte d'Ivoire, and the Czech Republic support the usefulness of the analytic framework. The assessment concludes that the policy relevance of voucher programs for developing economies remains uncertain. Major voucher initiatives have been attempted only in countries with a well-developed institutional infrastructure. Some studies find favorable benefits for at least some population groups, but others find limited effects and evidence of increasing social stratification in schools. Whether vouchers lead to better outcomes or greater stratification appears related to specific contexts, institutional variables, and program designs.